The Transformation of The Government's Digital Political Communication: A Study of The Relationship Between The Indonesian Communications Agency and Homeless Media - Andika Handayani; Paradiba Aslam; Edison Bonartua Hutapea (International Journal Labs, 2026)
This study examines the integration of government political communication with digital media platforms, focusing on the role of homeless media accounts and counter-narratives in shaping public perceptions. The research highlights how government programs, traditionally delivered through formal and bureaucratic channels, are now repackaged into digital content such as short videos, infographics, memes, and pop culture elements to align with social media algorithms. Using a case study of 40 homeless media accounts announced under INMF, this study analyzes how 27 of these accounts provide counter-narratives “statements of attitude” to quickly influence public discourse, generate speculation, and challenge dominant narratives. The findings reveal that immediacy, diversity of cues (visual, audio, textual), multilingual communication (Indonesian and English), and direct personal interactions are key factors enhancing audience engagement and political communication effectiveness. From a programmable politics perspective, these results illustrate the government’s increasing reliance on platform mechanisms and digital engagement logic, emphasizing the shift from top-down, bureaucratic communication to participatory, digitally mediated communication. The study contributes to understanding how digital media reshapes political communication, public perception management, and symbolic resistance through social media, providing practical insights for government communication strategies in the digital era.